2016
DOI: 10.1021/acsami.6b11108
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric and Triboelectric Dual Effects in Mechanical-Energy Harvesting Using BaTiO3/Polydimethylsiloxane Composite Film

Abstract: Piezoelectric and triboelectric nanogenerators have been developed as rising energy-harvesting devices in the past few years to effectively convert mechanical energy into electricity. Here, a novel hybrid piezo/triboelectric nanogenerator based on BaTiO NP/PDMS composite film was developed in a simple and low-cost way. The effects of the BTO content and polarization degree on the output performance were systematically studied. The device with 20 wt % BTO in PDMS and a 100-μm-thick film showed the highest outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(136 citation statements)
references
References 27 publications
2
133
1
Order By: Relevance
“…It is found that the accordant direction of piezoelectric polarized charges and triboelectric induced charges would enhance power outputs, while their opposite direction would tremendously reduce electricity generation. According to the number of electrodes and combination ways of PENG and TENG, there are three different coupling modes of PTHNGs ( Figure a), i.e., mode I in which PENG and TENG share a pair of electrodes, mode II in which PENG and TENG share one common electrode, and mode III in which PENG and TENG work independently . Although each mode has its own characteristics, their electrical generation processes can be roughly divided into three steps, i.e., 1) TENG contacted and PENG pressed, 2) TENG contacted and PENG released, or 3) TENG separated and PENG released, according to the contact or separation state of triboelectric material and the compress or release state of piezoelectric material.…”
Section: Textile‐based Piezoelectric and Triboelectric Hybrid Nanogenmentioning
confidence: 99%
“…It is found that the accordant direction of piezoelectric polarized charges and triboelectric induced charges would enhance power outputs, while their opposite direction would tremendously reduce electricity generation. According to the number of electrodes and combination ways of PENG and TENG, there are three different coupling modes of PTHNGs ( Figure a), i.e., mode I in which PENG and TENG share a pair of electrodes, mode II in which PENG and TENG share one common electrode, and mode III in which PENG and TENG work independently . Although each mode has its own characteristics, their electrical generation processes can be roughly divided into three steps, i.e., 1) TENG contacted and PENG pressed, 2) TENG contacted and PENG released, or 3) TENG separated and PENG released, according to the contact or separation state of triboelectric material and the compress or release state of piezoelectric material.…”
Section: Textile‐based Piezoelectric and Triboelectric Hybrid Nanogenmentioning
confidence: 99%
“…Different kinetic energy conversion methods in combination are able to compensate each other, thus boosting the output power. Various types of kinetic (including fluidic) hybridization involving two energy conversion effects have been developed, including piezoelectric–electromagnetic, electrostrictive–electrets, piezoelectric–triboelectric, electromagnetic–triboelectric, piezoelectric–electrostatic, triboelectric–electrostatic, and piezoelectric–electrostrictive . Hybridization involving three kinetic energy conversion effects, piezoelectric–electromagnetic–triboelectric, has also been reported.…”
Section: Hybridization Of Energy Harvestersmentioning
confidence: 99%
“…[114] Under bending excitation at approximately 45 Hz, an output peak-to-peak voltage of approximately 0.45 V under a load resistance of 1 MΩ was obtained. [116] The effects of the contents of multi-walled carbon nanotubes (MWCNT) (0.0-5.0 wt%) and BaTiO 3 nanofibers (10-50 wt%) on the electrical, dielectric, and piezoelectric properties of PDMS-based nanogenerators were systematically investigated. [115] A BaTiO 3 /PDMS composite film with a 20 wt% mass ratio of BaTiO 3 nanoparticles exhibited the highest performance (output voltage of approximately 14 V).…”
Section: Non-piezoelectric Polymer With Batiomentioning
confidence: 99%
“…[115] A BaTiO 3 /PDMS composite film with a 20 wt% mass ratio of BaTiO 3 nanoparticles exhibited the highest performance (output voltage of approximately 14 V). [116] The effects of the contents of multi-walled carbon nanotubes (MWCNT) (0.0-5.0 wt%) and BaTiO 3 nanofibers (10-50 wt%) on the electrical, dielectric, and piezoelectric properties of PDMS-based nanogenerators were systematically investigated. [117] A nanocomposite with 2.0 wt% MWCNTand 40 wt% BaTiO 3 nanofiber generated the highest output voltage of approximately 3.73 V, a current of approximately 1.37 mA, and a power of approximately 330 μW, which was sufficient to light up commercial LEDs and charge a capacitor after rectification.…”
Section: Non-piezoelectric Polymer With Batiomentioning
confidence: 99%